Comparison of Different Methods of Denim Stone Washing by Pumice Stone, Acid Cellulases and Neutral Cellulases - M. Montazer; A. Sadeghian Maryan (علوم و تکنولوژی پلیمر, 2007)
Denim is a casual garment normally used by young people and extremely influential in shaping the fashion industry. Among various garments, these garments are subjected to innovations. This work is an attempt to compare the different methods of stone washing using pumice stones, acid cellulases and neutral cellulases or in combination of these methods. The effects of different processing conditions on the garment are compared and reported. Color differences of samples are probed by reflective colorimeter on the front side as well as the backside and also the white pocket of the garment.The abrasion resistance, tensile strength and crease recovery angle of samples are also reported. The XRD spectra are used to calculate the crystalline degrees of the selected samples. Moreover, fiber surfaces of some treated samples have been observed by SEM. The results indicate that treatment of denim with pumice stone with equal weight of garment causes a small color differences. The addition of cellulases to the washing, however, accelerates the color fading. Also, lower staining observed on the white pocket when the garment was treated with cellulases. However, the neutralcellulases increase the garment fading and decrease the staining on the white pocket. It is also observed that pumice stone with cellulases damages the fabric surface, although it is of a minimal damage.